Leadership Strategies for Teachers' Social Competence Development Through Pesantren Values Integration in East Lombok Islamic Schools - Zaetullah, Zaetullah; Harmonika, Sri; Yahya, Fizian (JSP: Jurnal Studi Pesantren, 2025)
Teachers' social competence is a fundamental yet often overlooked dimension of educational quality in Islamic educational institutions. Without strategic leadership grounded in strong values, this competence tends to develop inconsistently, resulting in ineffective teacher interactions with students, colleagues, parents, and the broader community. This study aims to analyze leadership strategies in developing teachers' social competence through pesantren values integration at an Integrated Islamic School in East Lombok, West Nusa Tenggara, Indonesia. A qualitative descriptive approach was employed, with data collected through in-depth interviews with the principal, teachers, and students, complemented by observation and documentation, and analyzed using the Miles and Huberman model through source and technique triangulation. The findings reveal four leadership strategies rooted in pesantren values: serving as a motivator through appreciation and moral support; functioning as a facilitator through training programs and collaborative activities; modeling exemplary behavior reflecting discipline and mutual respect; and building a collaborative culture through regular coordination and team-based tasks. Supporting factors include active teacher participation and adequate facilities, while inhibiting factors include low motivation among some teachers and heavy teaching schedules. Leadership strategies grounded in pesantren values contribute significantly to teachers' social competence development and the creation of a conducive educational climate.